Nutrient Concentrations in Big Creek Correlate to Regional Watershed Land Use. Issue 1 (1st October 2017) - Sharpley, A. N.; Haggard, B. E.; Berry, L.; Brye, K.; Burke, J.; Daniels, M. B.; Gbur, E.; Glover, T.; Hays, P.; Kresse, T.; VanDevender, K. W.
Abstract : Core Ideas: Nutrient concentrations are low at Big Creek relative to expected biological‐response thresholds. Nutrient concentrations at Big Creek are typical of streams draining watersheds with similar land use. Flow‐adjusted nutrient concentrations at Big Creek have not increased over the short‐term. Nutrient concentrations in streams increase as watershed land area in pasture and urban uses increases. Nutrient concentrations in several streams of the Boston and Ozark Mountains region of Arkansas, including the Buffalo National River and its tributaries, have garnered tremendous interest. In particular, Big Creek has been the center of attention within the Buffalo River watershed because of a permitted concentrated animal feeding operation (CAFO). The objectives of this paper were to put nutrient concentrations of Big Creek into the context of the stream nutrient and watershed land‐use relationship and develop a framework to evaluate regional land‐use impacts on regional water quality. Nutrient concentrations in streams draining the Boston and Ozark Mountains region were related to the intensity of watershed land use. Concentrations in Big Creek were similar to other watersheds in the ecoregion with similar land use, suggesting limited impact of the CAFO on Big Creek at the present time. However, this does not preclude future impacts, and longer‐term monitoring continues.